A historical approach to English for Specific Purposes in - Pibaque Pionce , Maritza Sandra; Quevedo Arnaiz , Ned; Colunga Santo , Silvia (Transformación, 2024)
The systematization of experiences in the process of doctoral training in Educational Sciences, allows proposing the historical analysis of English for Specific Purposes in Ecuador, preferably in International Business Degree students, as the basis for the theoretical analysis for the scientific assessment of educational research works. The definition and justification for the periods established in time are presented, which aims at assessing the historical development of the teaching-learning process of English for Specific Purposes related to business formation, upon which is necessary to address the effectiveness of teaching English. Thus the lingo-cultural competence focuses on the ability to negotiate cultural meanings and implement effective communication behaviors concentrating connected aspects of languages directly with specific cultural facts of a society. This research work has been based on bibliography analysis, inductive - deductive and analysis – synthesis methods.
Keywords: Teaching learning; English for Specific Purposes; Training and development of the lingo-cultural competence